PENGEMBANGAN MULTIMEDIA INTERAKTIF PADA PEMBELAJARAN PANCASILA KELAS IV SEKOLAH DASAR - Nugraha, Ignasius Bayu Setya; Ashari, Ashari; Suyoto, Suyoto (Yayasan Panca Bakti Wiyata Pangandaran, 2024)
Research has been carried out with the aim of: 1) producing interactive multimedia in class IV elementary school Pancasila learning, and 2) determining the feasibility of interactive multimedia in class IV elementary school Pancasila learning. This development uses research methods (R&D) with ADDIE stages (Analyze, Design, Development, Implementation and Evaluation). In the Analyze stage, activities are carried out, namely analyzing the curriculum, needs, learning media and materials. In the Design Stage, the activities carried out are collecting references, designing interactive multimedia designs, compiling layouts, compiling materials, and compiling evaluation questions. Development stage (design) activities carried out to develop interactive multimedia in Pancasila learning for class IV elementary schools. The implementation phase involves product trials on students with limited trials and extensive trials. Data collection techniques use observation, interviews, questionnaires and tests. The research subjects were fourth grade students at SD Tahfidzul Qur'an Nuurul Waahid Purworejo. The research results are as follows: 1) producing interactive multimedia in Pancasila learning for class IV elementary schools. 2) The results of the feasibility of interactive multimedia consist of: a) validity. The percentage of material experts is 75%, media experts are 95%, and practitioners are 91% in the feasible and very feasible categories. b) the practicality of the student response from limited trials got 96% and extensive trials got 95%. The results of learning implementation at the first meeting, observer I got a percentage of 93% and observer II got a percentage of 93% which was categorized as very good. Meeting II from the results of observers I and II received a percentage of 86% which was categorized as very good. c) effectiveness is obtained from N-Gain analysis using the Guttman scale by getting a gain score of 0.75, categorized as g> 0.7 in the high category. Based on these results, interactive multimedia is said to be feasible and effective to use to help educators convey lesson material, make it easier for students to understand the material presented, and improve the quality of learning in class IV of the Purworejo Tahfidzul Qur'an Elementary School.